Textile Dyeing - Peter J. Hauser (IntechOpen, 2011)
The coloration of fibers and fabrics through dyeing is an integral part of textile manufacturing. This book discusses in detail several emerging topics on textile dyeing. ""Textile Dyeing"" will serve as an excellent addition to the libraries of both the novice and expert.
English
Keywords: Physical Sciences; Engineering and Technology; Technology; Textile Engineering; Fabric Engineering